2017
DOI: 10.3390/universe3010026
|View full text |Cite
|
Sign up to set email alerts
|

Cosmology with Varying Constants from a Thermodynamic Viewpoint

Abstract: Abstract:We study the variation of fundamental constants in cosmology while dealing with thermodynamic aspects of gravity. We focus on the variation of the speed of light, c, and Newton's gravitational constant, G, with respect to cosmic time. We find the constraints on the possible variation of these constants by comparing varying constants of cosmological models with the latest observational data.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…We believe most of the negative findings on the variation of physical constants are possibly due to the variation of a constant being considered in isolation rather than holistically for all the constants involved. We have established that the physical constants not only vary but also how much they vary: H/H = −0.6 H. In addition, from the null results on the variation of the fine structure constant [14,15], we have shown that . h/h = 1.8H.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations
“…We believe most of the negative findings on the variation of physical constants are possibly due to the variation of a constant being considered in isolation rather than holistically for all the constants involved. We have established that the physical constants not only vary but also how much they vary: H/H = −0.6 H. In addition, from the null results on the variation of the fine structure constant [14,15], we have shown that . h/h = 1.8H.…”
Section: Discussionmentioning
confidence: 67%
“…The orbit of Earth around the sun is Keplerian and thus is governed by Equation (15). A radiometric measurement will therefore yield a null result in our approach using evolutionary G and c. However, the eccentricity evolution is equally valid for the moon and Earth.…”
Section: Astronomical Unit (Au) Anomalymentioning
confidence: 99%
See 2 more Smart Citations
“…Rosenband et al [14] have put a constraint on the ̇/ = (−1.6 ± 2.3) × 10 −17 yr −1 derived from the constancy of the ratio of aluminum and mercury single-ion optical clock frequencies. More recently Gohar [15], using his entropic model of the universe and data on supernovae 1a, baryon acoustic oscillations, and cosmic microwave background, has established even more stringent constraint on the variation of . Additionally, he states that in his model and should be increasing with the evolution of the universe, which corroborates our findings in this work.…”
Section: Introductionmentioning
confidence: 99%